Model Pengembangan Konten Digital Moderat sebagai Upaya Preventif Radikalisme di Lingkungan Remaja Masjid di Tulungagung - Wardiana, Uswah; Hadi, Dzinnun (Kartika: Jurnal Studi Keislaman, 2026)
In the digital era, the challenges to religious moderation have intensified due to the proliferation of radical content on social media, which has the potential to influence young people’s religious understanding, tolerance attitudes, and ideological orientation. This study aims to strengthen the values of religious moderation through the digitization of content responsive to radicalism, particularly among the youth of Baitul Hakim Mosque in Tulungagung. The method employed is the Asset-Based Community Development (ABCD) approach, which emphasizes the utilization of human and technological assets as media for the production and dissemination of moderation-based content. The program involved a series of training sessions and discussions covering self-analysis, religious moderation, mosque activism, social media utilization, and digital content production techniques. As a result, a community of digital creators and mosque da’wah activists was established, capable of producing and disseminating moderation-oriented content through the Instagram platform @aktivisdakwahmasjid. Digital literacy was implemented to enhance critical skills in filtering information and educating the public about the dangers of radicalism. The findings highlight the importance of strengthening digital literacy and innovation-based communication rooted in moderation values to minimize the impact of radical content on social media. The implications suggest that similar programs can be implemented sustainably as a contribution of the ABCD-based model, reinforcement of moderate digital da’wah, and replication of the model in other campus mosques.